Anti-cracking inorganic high-molecular silicon-aluminum polymer admixture as well as preparation method and application of anti-cracking inorganic high-molecular silicon-aluminum polymer admixture

By using crack-resistant inorganic polymer silicon-aluminum polymer admixture in cement concrete, the cracking problem caused by volume shrinkage stress in cement concrete is solved, and the effect of significantly improving the tensile strength and crack resistance of concrete is achieved.

CN119797796AActive Publication Date: 2025-04-11UNIV OF JINAN
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202510048093.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-13
Publication Date
2025-04-11
Estimated Expiration
2045-01-13

AI Technical Summary

Technical Problem

The volume shrinkage stress generated by cement concrete during hydration and drying leads to concrete cracking. The existing fiber and expansion agent incorporation methods have limitations and cannot effectively improve the crack resistance of concrete.

Method used

A crack-resistant inorganic polymer silicon-aluminum polymer admixture is used. This admixture reacts in situ with Ca2+ in the early stage of concrete hydration to form a high-strength gelling product and improve the tensile strength of concrete.

Benefits of technology

By forming high-strength gelling products, the tensile strength and crack resistance of concrete are significantly improved, the risk of concrete cracking is reduced, and the overall strength and durability of concrete are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119797796A_ABST
    Figure CN119797796A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of concrete admixtures, and particularly discloses an anti-crack inorganic polymer silicon-aluminum polymer admixture as well as a preparation method and application thereof. The method comprises the following steps: (1) adding an alkalizer and a co-stabilizer into an aluminum sulfate solution, and carrying out continuous stirring treatment under heating and heat preservation conditions to obtain a precursor solution; and (2) adding diethanolisopropanolamine into the precursor liquid, continuously stirring under the conditions of heating and heat preservation, standing the obtained reaction liquid to naturally precipitate, and taking the supernate after the reaction is completed. And (3) heating the supernate, adding fluosilicic acid under a stirring condition, and then preserving heat to obtain the admixture. The inorganic high-molecular silicon-aluminum polymer admixture obtained by the invention can be subjected to in-situ reaction with a large amount of Ca < 2 + > generated by hydration reaction at the early hardening stage of concrete to form a high-strength gelling product, so that the tensile strength of the concrete is improved, and the crack resistance of the concrete is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of concrete admixtures, and in particular to an anti-cracking inorganic macromolecular silicon-aluminum polymer admixture and a preparation method and application thereof. Background Art

[0002] The information disclosed in this background technology section is only intended to enhance the understanding of the overall background of the invention, and should not necessarily be regarded as an admission or any form of suggestion that the information constitutes the prior art already known to a person skilled in the art.

[0003] Cement concrete has the advantages of high strength, high hardness and low cost, and is widely used in the field of infrastructure construction. However, since the chemical shrinkage caused by cement hydration and the drying shrinkage caused by water evaporation are difficult to avoid, the volume shrinkage of cement concrete is its essential property. This causes shrinkage stress to be generated when the shrinkage of concrete is constrained. When the shrinkage stress is large and higher than the tensile strength of the concrete itself, it will cause concrete cracking. Concrete cracks will seriously affect the service safety, reliability and service life of its structural engineering. Sometimes it can even lead to sudden damage to the construction project and cause major safety accidents.

[0004] At present, the main means to improve the crack resistance of cement concrete is to add fibers or expansion agents to concrete, and both have achieved certain application effects. However, fiber materials neither participate in the hydration reaction of cement nor change the hydration and hardening process, and do not have any modification effect on the microstructure of concrete, so they cannot improve the strength and crack resistance of concrete itself. In addition, fibers are prone to aging, degradation, rust and other problems due to environmental influences. At the same time, they may also affect the workability of concrete, increase the viscosity of concrete, and bring difficulties to construction. Excessive dosage of expansion agents or improper use will lead to deterioration of concrete performance, especially when the quality of concrete raw materials fluctuates greatly and the mix ratio is frequently adjusted. Coupled with unfavorable factors such as large changes in the construction environment and irregular operations, the expansion agent sometimes has the problem of "delayed expansion", which in turn causes concrete cracking. Summary of the invention

[0005] In view of the above problems, the present invention provides an anti-cracking inorganic high molecular silicon aluminum polymer admixture and its preparation method and application. The admixture can react with a large amount of Ca2+ produced by hydration reaction in the early stage of concrete hardening. 2+ An in-situ reaction is carried out to form a high-strength cementitious product, thereby increasing the tensile strength of the concrete and thus improving the crack resistance of the concrete itself. Specifically, the present invention discloses the following technical solutions.

[0006] First, the present invention discloses an anti-cracking inorganic high molecular silicon aluminum polymer admixture, the effective ingredients of which include the ingredients shown in formula (1): Formula (1).

[0007] Furthermore, in the formula (1), n=10~20.

[0008] Secondly, the preparation method of the anti-cracking inorganic macromolecular silicon-aluminum polymer admixture disclosed in the present invention comprises the following steps: (1) Take aluminum sulfate solution, alkalizer, stabilizer, diethanol monoisopropanolamine and fluorosilicic acid as raw materials for use.

[0009] (2) Adding the alkalizing agent and the stabilizer to the aluminum sulfate solution, and continuously stirring the solution under heating and heat preservation conditions, to obtain a precursor liquid.

[0010] (3) Adding the diethanol monoisopropanolamine to the precursor liquid and continuously stirring the mixture under heating and heat preservation conditions, then allowing the obtained reaction liquid to stand for natural precipitation, and collecting the supernatant after completion.

[0011] (4) After heating the supernatant, adding the fluorosilicic acid under stirring conditions, and then keeping the temperature, after completion, the inorganic high molecular weight silicon aluminum polymer admixture is obtained.

[0012] Furthermore, in step (1), the proportions of the components in the raw materials are: 80-92 parts by weight of aluminum sulfate solution, 0.8-3.9 parts by weight of alkalizer, 0.5-1.9 parts by weight of stabilizer, 0.6-3.6 parts by weight of diethanol monoisopropanolamine, and 5.8-8.7 parts by weight of fluorosilicic acid.

[0013] Furthermore, in step (1), the mass fraction of the aluminum sulfate solution is 21-33%.

[0014] Furthermore, in step (1), the mass fraction of fluorosilicic acid is 30-32%.

[0015] Furthermore, in step (1), the alkalizing agent includes at least one of calcium hydroxide, sodium bicarbonate, etc.

[0016] Furthermore, in step (1), the co-stabilizer includes at least one of acetic acid, citric acid, etc.

[0017] Furthermore, in step (2), the heating and heat preservation temperature is 70-80° C., and the continuous stirring treatment time is 3-4 hours.

[0018] Furthermore, in step (3), the heating and heat preservation temperature is 60-76° C., and the continuous stirring treatment time is 1-2 hours.

[0019] Furthermore, in step (3), the standing time is not less than 18 hours to remove the calcium sulfate product formed by the reaction.

[0020] Furthermore, in step (4), the heating temperature is 58-64° C., and the insulation time is 1-2 hours.

[0021] Again, the present invention discloses the use of the anti-cracking inorganic macromolecular silica-alumina polymer admixture in silicate cement-based materials. Optionally, the admixture dosage is 0.1-0.2% of the silicate cement component.

[0022] Compared with the prior art, the technical solution of the present invention has at least the following beneficial effects: 1. The present invention uses polyaluminium sulfate as the matrix and uses fluorosilicic acid to introduce silicon atoms to obtain a crack-resistant inorganic high molecular silicon-aluminium polymer, which effectively improves the mechanical strength of the concrete structure itself and reduces the risk of cracking of the concrete structure. This is because: (1) In the early stage of concrete hydration and hardening, the admixture will hydrolyze to form aluminum ions (Al 3+ ), hydroxyaluminum group (Al(OH) 2+ 、Al(OH) 2+ 、Al(OH) 4- 、Al 13 O4(OH) 24 7+ ), sulfate ion (SO4 2+ ), polysilicic acid groups (SiO x ), these active substances release a large amount of Ca2+ during cement hydration. 2+ In-situ reaction is carried out to generate high-strength micro-expanded needle-rod-shaped calcium sulfoxide and high-strength long-chain hydration product CSH gel. The needle-rod-shaped calcium sulfoxide is interspersed in the concrete to form a three-dimensional spatial network with a continuous structure, providing a continuous skeleton for the attachment of CSH gel. These two cementitious products work together to effectively improve the tensile strength of the concrete itself, thereby improving the concrete's resistance to cracking.

[0023] (2) The micro-expanding needle-shaped calcium sulfonate and CSH gel are both highly hydrated compounds. During their formation, they consume part of the free water in the concrete system, which is equivalent to reducing the water-cement ratio of the concrete, and can effectively reduce the water seepage rate, porosity and capillary shrinkage stress of the concrete. At the same time, the micro-expansion characteristics of calcium sulfonate can effectively compensate for the shrinkage of concrete, improve the volume stability of concrete, and thus reduce the risk of concrete cracking. In addition, since the calcium sulfonate contains a large number of water molecules in its own structure and can retain free water about twice its own weight, it can consume the free water in the concrete and reduce the cracking caused by the drying shrinkage of the concrete due to water evaporation.

[0024] 2. The admixture prepared by the present invention can maintain long-term stability without adding other stabilizers, preventing coagulation during storage. This is because the present invention utilizes the arc pair electrons on the N atom in the diethanol monoisopropanolamine, which can coordinate with the Al atom in the admixture to stabilize Al. At the same time, the -OH on the diethanol monoisopropanolamine can not only provide electrons to stabilize the Al atom, but also combine with the hydrated hydroxyaluminum in the solution through hydrogen bonds to stabilize it, preventing it from over-aggregating or forming unstable polymers. The acetic acid helps to inhibit the Al in the admixture 3+ hydrolysis, thereby preventing the formation of unstable precipitates or undesirable polymer structures.

[0025] The use of the admixture of the present invention can not only effectively control the generation of cracks in the concrete structure, but also improve the overall strength of the concrete structure, which means that the durability and stability of the concrete structure when subjected to loads and external environmental influences are significantly enhanced, making its performance even better under various complex engineering conditions. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] The accompanying drawings in the specification, which constitute a part of the present invention, are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute improper limitations on the present invention.

[0027] Figure 1 This is a sample of the inorganic high molecular weight silicon-aluminum polymer admixture prepared in the following Example 1.

[0028] Figure 2 The following is a graph showing the pore distribution results in the concrete specimens prepared in Examples 1 to 5. DETAILED DESCRIPTION

[0029] The present invention will be further described below in conjunction with specific examples. It should be understood that these examples are only used to illustrate the present invention and are not intended to limit the scope of the present invention. The experimental methods in the following examples without specifying specific conditions are usually carried out under conventional conditions or under conditions recommended by the manufacturer.

[0030] Unless otherwise defined, all professional and scientific terms used in the present invention have the same meanings as those familiar to those skilled in the art. The reagents or raw materials used in the present invention can be purchased through conventional channels. Unless otherwise specified, the reagents or raw materials used in the present invention are used in a conventional manner in the art or in accordance with the product instructions.

[0031] In addition, any method and material similar or equivalent to the described content can be applied to the method of the present invention. The technical solution of the present invention is further described in conjunction with the accompanying drawings and specific embodiments.

[0032] Example 1 A method for preparing a crack-resistant inorganic macromolecular silicon-aluminum polymer admixture comprises the following steps: (1) Weigh the following raw materials for use: 85 parts by weight of 30% aluminum sulfate solution, 2.0 parts by weight of calcium hydroxide powder, 1.0 parts by weight of acetic acid, 2.5 parts by weight of diethanol monoisopropanolamine, and 7.4 parts by weight of 32% fluorosilicic acid.

[0033] (2) Add the calcium hydroxide powder and acetic acid to the aluminum sulfate solution, then heat to 76° C. in a water bath and stir continuously for 4 hours to obtain a precursor solution.

[0034] (3) Add the diethanol monoisopropanolamine to the precursor solution and continue to heat and stir at 76° C. for 2 hours, then let the resulting reaction solution stand for 24 hours, and take the supernatant after completion.

[0035] (4) After the supernatant is heated to 60° C., the fluorosilicic acid is added dropwise under stirring. After the addition is completed, the temperature is kept for 2 hours. After completion, an admixture is obtained, such as Figure 1 shown.

[0036] Performance test: (1) The admixture prepared in this embodiment is added to silicate cement concrete in an amount of 0.15% of the mass of the silicate cement component, and then the concrete is poured into a mold, demolded after hardening and forming, and placed in a standard curing box for curing for 28 days to obtain a concrete specimen. According to the "Test Method for Drying Shrinkage Cracking Performance of Cement Mortar and Concrete" (GB / T 29417-2012), the cracking index and drying shrinkage stress of the specimen are tested, and the results are cracking index = 24.18%, drying shrinkage stress = 0.96MPa. (2) According to the "Test Method for Strength of Cement Mortar (ISO Method)" (GB / T17671-2021), the flexural strength of the concrete specimen is tested, and the result is 9.46MPa. (3) The pore distribution of different scales in the concrete specimen is tested, and the results are as follows Figure 1 As shown. The harmful pores with a pore size greater than 1000nm will have a negative impact on the compressive strength and flexural strength. It can be seen that the proportion of pores with a size greater than 1000nm in this embodiment is relatively low.

[0037] Example 2 A method for preparing a crack-resistant inorganic macromolecular silicon-aluminum polymer admixture comprises the following steps: (1) Weigh the following raw materials for use: 92 parts by weight of 21% aluminum sulfate solution, 3.9 parts by weight of calcium hydroxide powder, 1.9 parts by weight of citric acid, 3.6 parts by weight of diethanol monoisopropanolamine, and 8.7 parts by weight of 30% fluorosilicic acid.

[0038] (2) Add the calcium hydroxide powder and citric acid to the aluminum sulfate solution, then heat to 70° C. in a water bath and stir continuously for 4 hours to obtain a precursor solution.

[0039] (3) Add the diethanol monoisopropanolamine to the precursor solution and continue to stir at 70° C. for 1.5 hours, then let the resulting reaction solution stand for 24 hours. After completion, take the supernatant.

[0040] (4) After the supernatant is heated to 58° C., the fluorosilicic acid is added dropwise under stirring. After the addition is completed, the temperature is kept for 2 hours to obtain an admixture.

[0041] Performance test: (1) The admixture prepared in this embodiment is added to silicate cement concrete in an amount of 0.2% of the mass of the silicate cement component, and then the concrete is poured into a mold, demolded after hardening and forming, and placed in a standard curing box for curing for 28 days to obtain a concrete specimen. According to the "Test Method for Drying Shrinkage Cracking Performance of Cement Mortar and Concrete" (GB / T 29417-2012), the cracking index and drying shrinkage stress of the specimen are tested, and the results are cracking index = 44.27%, drying shrinkage stress = 1.53MPa. (2) According to the "Test Method for Strength of Cement Mortar (ISO Method)" (GB / T17671-2021), the flexural strength of the concrete specimen is tested, and the result is 9.33MPa. (3) The pore distribution of different scales in the concrete specimen is tested, and the results are as follows Figure 1 As shown. The harmful pores with a pore size greater than 1000nm will have a negative impact on the compressive strength and flexural strength. It can be seen that the proportion of pores with a size greater than 1000nm in this embodiment is relatively low.

[0042] Example 3 A method for preparing a crack-resistant inorganic macromolecular silicon-aluminum polymer admixture comprises the following steps: (1) Weigh the raw materials according to the following proportions and set aside: 80 parts by weight of 33% aluminum sulfate solution, 0.8 parts by weight of calcium hydroxide powder, 0.5 parts by weight of acetic acid, 0.6 parts by weight of diethanol monoisopropanolamine, and 5.8 parts by weight of 32% fluorosilicic acid.

[0043] (2) Add the calcium hydroxide powder and acetic acid to the aluminum sulfate solution, then heat to 80° C. in a water bath and stir continuously for 3 hours to obtain a precursor solution.

[0044] (3) Add the diethanol monoisopropanolamine to the precursor solution, keep it warm at 60° C. and stir it continuously for 1 hour, then let the resulting reaction solution stand for 18 hours, and take the supernatant after completion.

[0045] (4) After the supernatant is heated to 64° C., the fluorosilicic acid is added dropwise under stirring. After the addition is completed, the temperature is kept for 1 hour to obtain an admixture.

[0046] Performance test: (1) The admixture prepared in this embodiment is added to silicate cement concrete in an amount of 0.1% of the mass of the silicate cement component, and then the concrete is poured into a mold, demolded after hardening and forming, and placed in a standard curing box for curing for 28 days to obtain a concrete specimen. According to the "Test Method for Drying Shrinkage Cracking Performance of Cement Mortar and Concrete" (GB / T 29417-2012), the cracking index and drying shrinkage stress of the specimen are tested, and the results are cracking index = 48.61%, drying shrinkage stress = 1.82MPa. (2) According to the "Test Method for Strength of Cement Mortar (ISO Method)" (GB / T17671-2021), the flexural strength of the concrete specimen is tested, and the result is 9.05MPa. (3) The pore distribution of different scales in the concrete specimen is tested, and the results are as follows Figure 1 As shown. The harmful pores with a pore size greater than 1000nm will have a negative impact on the compressive strength and flexural strength. It can be seen that the proportion of pores with a size greater than 1000nm in this embodiment is relatively low.

[0047] Example 4 A method for preparing a crack-resistant inorganic macromolecular silicon-aluminum polymer admixture comprises the following steps: (1) Weigh the following raw materials for use: 85 parts by weight of 30% aluminum sulfate solution, 2.0 parts by weight of calcium hydroxide powder, 1.0 parts by weight of acetic acid, and 2.5 parts by weight of diethanol monoisopropanolamine.

[0048] (2) Add the calcium hydroxide powder and acetic acid to the aluminum sulfate solution, then heat to 76° C. in a water bath and stir continuously for 4 hours to obtain a precursor solution.

[0049] (3) Add the diethanol monoisopropanolamine to the precursor solution and continue to heat and stir at 76° C. for 2 hours, then let the resulting reaction solution stand for 24 hours. After completion, take the supernatant to obtain an admixture.

[0050] Performance test: (1) The admixture prepared in this embodiment is added to silicate cement concrete in an amount of 0.15% of the mass of the silicate cement component, and then the concrete is poured into a mold, demolded after hardening and forming, and placed in a standard curing box for curing for 28 days to obtain a concrete specimen. According to the "Test Method for Drying Shrinkage Cracking Performance of Cement Mortar and Concrete" (GB / T 29417-2012), the cracking index and drying shrinkage stress of the specimen are tested, and the results are cracking index = 69.61%, drying shrinkage stress = 2.44MPa. (2) According to the "Test Method for Strength of Cement Mortar (ISO Method)" (GB / T17671-2021), the flexural strength of the concrete specimen is tested, and the result is 7.91MPa. (3) The pore distribution of different scales in the concrete specimen is tested, and the results are as follows Figure 1 As shown. The harmful pores with a pore size greater than 1000nm will have a negative impact on the compressive strength and flexural strength. It can be seen that the proportion of pores with a size greater than 1000nm in this embodiment is higher than that in embodiments 1 to 3.

[0051] Example 5 A method for preparing a crack-resistant inorganic macromolecular silicon-aluminum polymer admixture comprises the following steps: (1) Weigh the following raw materials for use: 92 parts by weight of 21% aluminum sulfate solution, 3.9 parts by weight of calcium hydroxide powder, 1.9 parts by weight of citric acid, and 8.7 parts by weight of 30% fluorosilicic acid.

[0052] (2) Add the calcium hydroxide powder and citric acid to the aluminum sulfate solution, then heat to 70° C. in a water bath and stir continuously for 4 hours to obtain a precursor solution.

[0053] (3) After the precursor liquid is heated to 58° C., the fluorosilicic acid is added dropwise under stirring. After the addition is completed, the mixture is kept warm for 2 hours to obtain an admixture.

[0054] Performance test: (1) The admixture prepared in this embodiment is added to silicate cement concrete in an amount of 0.2% of the mass of the silicate cement component, and then the concrete is poured into a mold, demolded after hardening and forming, and placed in a standard curing box for curing for 28 days to obtain a concrete specimen. According to the "Test Method for Drying Shrinkage Cracking Performance of Cement Mortar and Concrete" (GB / T 29417-2012), the cracking index and drying shrinkage stress of the specimen are tested, and the results are cracking index = 56.20%, drying shrinkage stress = 2.13MPa. (2) According to the "Test Method for Strength of Cement Mortar (ISO Method)" (GB / T17671-2021), the flexural strength of the concrete specimen is tested, and the result is 8.41 MPa. (3) The pore distribution of different scales in the concrete specimen is tested, and the results are as follows Figure 1 As shown. The harmful pores with a pore size greater than 1000nm will have a negative impact on the compressive strength and flexural strength. It can be seen that the proportion of pores with a size greater than 1000nm in this embodiment is higher than that in embodiments 1 to 3.

[0055] Example 6 A method for preparing a crack-resistant inorganic macromolecular silicon-aluminum polymer admixture comprises the following steps: (1) Weigh the following raw materials for use: 80 parts by weight of 33% aluminum sulfate solution, 0.8 parts by weight of calcium hydroxide powder, 0.6 parts by weight of diethanol monoisopropanolamine, and 5.8 parts by weight of 32% fluorosilicic acid.

[0056] (2) Add the calcium hydroxide powder to the aluminum sulfate solution, then heat it to 80° C. in a water bath and stir it continuously for 3 hours to obtain a precursor solution.

[0057] (3) Add the diethanol monoisopropanolamine to the precursor solution and keep it at 60° C. and stir it continuously for 1 hour. Then, let the resulting reaction solution stand for 18 hours. After completion, take the supernatant.

[0058] (4) After the supernatant is heated to 64° C., the fluorosilicic acid is added dropwise under stirring. After the addition is completed, the temperature is kept for 1 hour to obtain an admixture.

[0059] Performance test: (1) The admixture prepared in this example is added to silicate cement concrete in an amount of 0.1% of the mass of the silicate cement component, and then the concrete is poured into a mold, demolded after hardening and forming, and placed in a standard curing box for curing for 28 days to obtain a concrete specimen. The cracking index and drying shrinkage stress of the specimen are tested according to the "Test Method for Drying Shrinkage Cracking Performance of Cement Mortar and Concrete" (GB / T 29417-2012), and the results are cracking index = 65.64%, drying shrinkage stress = 2.28MPa. (2) The flexural strength of the concrete specimen is tested according to the "Test Method for Strength of Cement Mortar (ISO Method)" (GB / T17671-2021), and the result is 8.27MPa.

[0060] Example 7 A method for preparing a crack-resistant inorganic macromolecular silicon-aluminum polymer admixture comprises the following steps: (1) Weigh the following raw materials for use: 92 parts by weight of 21% aluminum sulfate solution, 1.9 parts by weight of acetic acid, 3.6 parts by weight of diethanol monoisopropanolamine, and 8.7 parts by weight of 30% fluorosilicic acid.

[0061] (2) Add the acetic acid to the aluminum sulfate solution, then heat it to 80° C. in a water bath and stir it continuously for 3 hours to obtain a precursor solution.

[0062] (3) Add the diethanol monoisopropanolamine to the precursor solution, keep it warm at 60° C. and stir it continuously for 1 hour, then let the resulting reaction solution stand for 24 hours, and take the supernatant after completion.

[0063] (4) After the supernatant is heated to 64° C., the fluorosilicic acid is added dropwise under stirring. After the addition is completed, the temperature is kept for 1 hour to obtain an admixture.

[0064] Performance test: (1) The admixture prepared in this embodiment is added to silicate cement concrete in an amount of 0.1% by mass of the silicate cement component, and then the concrete is poured into a mold, demolded after hardening and forming, and placed in a standard curing box for curing for 28 days to obtain a concrete specimen. According to the "Test Method for Drying Shrinkage Cracking Performance of Cement Mortar and Concrete" (GB / T 29417-2012), the cracking index and drying shrinkage stress of the specimen are tested, and the results are cracking index = 66.67%, and drying shrinkage stress = 2.36MPa. (2) According to the "Test Method for Strength of Cement Mortar (ISO Method)" (GB / T17671-2021), the flexural strength of the concrete specimen is tested, and the result is 8.12MPa, The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention is described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A crack-resistant inorganic macromolecular silicon-aluminum polymer admixture, characterized in that: The active ingredients of the admixture include the ingredients shown in formula (1): Formula (1).

2. The anti-cracking inorganic macromolecular silicon-aluminum polymer admixture according to claim 1, characterized in that: In the formula (1), n=10~20.

3. A method for preparing a crack-resistant inorganic macromolecular silicon-aluminum polymer admixture, characterized in that: The steps include: (1) Take aluminum sulfate solution, alkalizer, stabilizer, diethanol monoisopropanolamine and fluorosilicic acid as raw materials for use; (2) adding the alkalizing agent and the stabilizer to the aluminum sulfate solution, and continuously stirring the solution under heating and heat preservation conditions to obtain a precursor liquid; (3) adding the diethanol monoisopropanolamine to the precursor liquid and continuously stirring the precursor liquid under heating and heat preservation conditions, and then allowing the obtained reaction liquid to stand for natural precipitation, and taking the supernatant after completion; (4) After heating the supernatant, adding the fluorosilicic acid under stirring conditions, and then keeping the temperature, after completion, the inorganic high molecular weight silicon aluminum polymer admixture is obtained.

4. The method for preparing the crack-resistant inorganic macromolecular silicon-aluminum polymer admixture according to claim 3, characterized in that: In step (1), the proportions of the components in the raw materials are: 80-92 parts by weight of aluminum sulfate solution, 0.8-3.9 parts by weight of alkalizer, 0.5-1.9 parts by weight of stabilizer, 0.6-3.6 parts by weight of diethanol monoisopropanolamine, and 5.8-8.7 parts by weight of fluorosilicic acid; Optionally, in step (1), the mass fraction of the aluminum sulfate solution is 21-33%; Optionally, in step (1), the mass fraction of fluorosilicic acid is 30-32%.

5. The method for preparing the crack-resistant inorganic macromolecular silicon-aluminum polymer admixture according to claim 3, characterized in that: In step (1), the alkalizing agent includes at least one of calcium hydroxide and sodium bicarbonate.

6. The method for preparing the crack-resistant inorganic macromolecular silicon-aluminum polymer admixture according to claim 3, characterized in that: In step (1), the co-stabilizer includes at least one of acetic acid and citric acid.

7. The method for preparing the crack-resistant inorganic macromolecular silicon-aluminum polymer admixture according to claim 3, characterized in that: In step (2), the heating and heat preservation temperature is 70-80°C, and the continuous stirring treatment time is 3-4 hours; Optionally, in step (3), the heating and heat preservation temperature is 60-76° C., and the continuous stirring treatment time is 1-2 hours.

8. The method for preparing the anti-cracking inorganic macromolecular silicon-aluminum polymer admixture according to any one of claims 2 to 7, characterized in that: In step (3), the standing time is not less than 18 hours.

9. The method for preparing the anti-cracking inorganic macromolecular silicon-aluminum polymer admixture according to any one of claims 2 to 7, characterized in that: In step (4), the heating temperature is 58-64° C. and the insulation time is 1-2 hours.

10. Use of the anti-cracking inorganic high molecular weight silica-alumina polymer admixture according to claim 1, or the admixture obtained by the preparation method according to any one of claims 2 to 9 in silicate cement-based materials; optionally, the admixture dosage is 0.1-0.2% of the silicate cement component.

Citation Information

Patent Citations

  • Concrete anti-cracking repairing agent and concrete applying the same

    CN103145365A

  • Preparation method of multifunctional efficient concrete water-proofing agent

    CN103755213A

  • Alkali-free liquid accelerator and preparation method thereof

    CN107601943A

  • Aluminum-based concrete microcrack self-repairing material, composition and preparation method and application of aluminum-based concrete microcrack self-repairing material

    CN115215574A

  • Early-strength anti-crack road concrete and preparation method thereof

    CN117486557A